The Effect of Ophiopogonin C in Ameliorating Radiation-Induced Pulmonary Fibrosis in C57BL/6 Mice: An Update Study - Fu, Xiaobin; Li, Tingting; Yao, Qiwei (Frontiers in Oncology, 2022)
Background The aim of this study was to assess and update the protective effects and underlying mechanisms of Ophiopogonin C (OP-C), a biologically active component separated and purified from Ophiopogon japonicus, in ameliorating radiation-induced pulmonary fibrosis in C57BL/6 mice administered thoracic radiation. Methods and Materials We randomly divided 75 mice into five groups and administered a dose of 12-Gy whole thoracic radiation to establish a pulmonary fibrosis animal model. Mice were treated with OP-C or dexamethasone combined with or without cephalexin by daily gavage for 4 weeks. All mice were sacrificed after the completion of thoracic irradiation at 28 weeks. Serum levels of interleukin-6 and transforming growth factor-β1 (TGF-β1) were evaluated. Moreover, superoxide dismutase (SOD) levels in lung tissue were measured. The severity of fibrosis was evaluated using the hydroxyproline content of the lung tissue. The pathological changes in the five groups were detected by hematoxylin and eosin and Masson trichrome staining. Smooth muscle actin expression was detected using immunohistochemical staining. Matrix metalloproteinases-2 (MMP-2) and tissue inhibitors of metalloproteases-2 (TIMP-2) were examined by immunohistochemical staining of the lung sections, and semiquantitative analysis was used to calculate the expression of MMP-2 and TIMP-2. Results Irradiated mice treated with OP-C or DXE combined with or without cephalexin significantly reduced mortality in mice and fibrosis levels by 1) reducing the deposition of collagen and accumulation of inflammatory cells and fibroblasts, 2) downgrading levels of the promote-fibrosis cytokine TGF-β1, and 3) increasing SOD activity in the lung tissue compared with that of irradiated mice without treatment. However, there were no statistical differences in fibrosis levels among the irradiated mice treated with OP-C or DXE combined with or without cephalexin. Conclusion OP-C significantly ameliorates radiation-induced pulmonary fibrosis and may be a promising therapeutic strategy for this disorder.